Management of the Headmaster in Increasing the Professionalism of the Staff - Wardah, Wardah; Suhardi, Suhardi; Sutrisno, Sutrisno (STAI Miftahul Ula Nganjuk, 2023)
This study aims to determine the management of the principal, the professionalism of the administrative staff, the management of the principal in increasing the professionalism of the administrative personnel and the supporting and inhibiting factors for the management of the principal in increasing the professionalism of the administrative staff at SMP Muhammadiyah Sentang. This research method is qualitative research. Data collection instruments used in this study were observation, interviews and documentation. The informants were school principals, teachers and administrative staff. Data analysis is done through data reduction, data display and verification. From the results of the study it is known that the management of school principals in improving teacher professionalism is carried out through principal planning which is carried out through meetings at the end of the current school year to develop school programs including the division of administrative work in the new academic year. Through this meeting, deficiencies, weaknesses, difficulties, or problems that are often experienced by administrative personnel in carrying out their duties can be identified. Organizing school principals in increasing the professionalism of administrative staff at SMP Muhammadiyah Sentang is carried out by determining the duties of administrative personnel in certain fields by issuing decrees and responsibilities that must be carried out. The principal's actions increased the professionalism of administrative staff at SMP Muhammadiyah Sentang by providing rewards for administrative staff who excelled, encouraging them to be better at carrying out their duties by participating in seminars. Supervision of school principals in increasing the professionalism of administrative staff at SMP Muhammadiyah Sentang is carried out through direct monitoring of the implementation of administrative staff duties. Supervision is also carried out by looking at the schedule and attendance list of the administrative staff and carrying out supervision as seen from the results of the work reports of the administrative staff at the end of the month.